Home Automation System Using Android and Internet (International Journal of Engineering and Computer Science, 2017)
The most clamant need of today’s generation, in view of the sedulous and busy life of people around, the need of some technique, which makes our life safe, and at the same time energy efficient. The concept of automation creeps from this very need-the need to control things to make life secure. But the attempts would be successful only with the right technology. We have started automating with this maiden effort of home automation. Home automation engulfs the idea of controlling lights and fan. The most luring feature which makes it so unique and particular beside the fact that it runs on world wide web is that it has the user end fixed as Android, which, today has emerged as the most lucrative and user friendly technology We have emulated this idea of combining Android platform along with Internet to save electricity. This maiden effort can well be applied to any electrical appliance since here we have restricted ourselves with switching on and off the lights and a fan along with controlling its speed. This automation system needs a dedicated computer machine, which serves the purpose at the spot of automation.